Temples, Tithes and Taxes: The Temple and Economic Life of Ancient Israel. By Marty Stevens - Goldhill, Simon (The journal of theological studies, 2008)
Marty Stevens, who teaches at the Lutheran Theological Seminary at Gettysburg, sets out to remind us that the temple in the ancient world was not just a place of worship but also an economic institution. With exemplary clarity and the verve of a good teacher she produces what she calls a synthetic model for the first millennium bce, which looks at temple personnel, temple income, temple expenses, and temple as ‘bank’, using Mesopotamian material as her prime comparison for the Temple of Jerusalem, her main concern. The resultant picture sees the Temple as an autonomous institution, which acts as a financial intermediary, facilitating loans and the circulation of wealth as well as receiving tithes and employing the local population.